Effect of the Structure and Mesoporosity in Ni/Zeolite Catalysts for n‐Hexadecane Hydroisomerisation and Hydrocracking. Issue 9 (20th April 2017) - Lanzafame, Paola; Perathoner, Siglinda; Centi, Gabriele; Heracleous, Elli; Iliopoulou, Eleni F.; Triantafyllidis, Konstantinos S.; Lappas, Angelos A.
Abstract: The hydroisomerisation/hydrocracking properties of Ni‐zeolite catalysts (H‐MFI and H‐Beta) are studied using n‐hexadecane as model compound and compared with those of Ni/ASA (amorphous silica‐alumina) as reference catalyst. In the case of H‐Beta, the effect of the introduction of mesoporosity by controlled desilication is also investigated. The results indicate that Ni on desilicated H‐Beta catalysts shows very interesting characteristics for the potential use in the production of biofuel from vegetable/algal oil, or the upgrading of biomass‐derived Fischer–Tropsch waxes. Ni/H‐Beta shows lower activity with respect to Ni/H‐MFI, but significantly lower formation of gases and much better hydroisomerisation activity. The introduction of mesoporosity by desilication enhances the activity, while still maintaining an acceptable gas formation and good hydroisomerisation properties. Furthermore, the desilication treatment improves the stability with respect to carbon formation. Abstract : Upgrading oil : Nickel on desilicated H‐Beta zeolite catalysts shows interesting characteristics that would be applicable for use in the production of biofuel from vegetable/algal oil, or the upgrading biomass‐derived of Fischer–Tropsch waxes.